The Politicization of Pesantren within the Framework of Athiyah al-Abrasyi’s Thought (An Analysis Based on the Book At-Tarbiyah al-Islamiyyah wa Falsafatuha) - Mohammad Zulkifli; Maimun Maimun (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
The problem addressed in this study is the gap between the ideal of holistic Islamic education and the phenomenon of politicization of Islamic boarding schools in the contemporary era, which has the potential to reduce the educational and spiritual role of these institutions. This study uses a qualitative approach with a philosophical-analytical library research method. Data collection techniques were carried out through documentary studies of primary sources, namely the book At-Tarbiyah al-Islamiyyah wa Falsafatuha by Athiyah al-Abrasyi, as well as secondary sources in the form of relevant literature on the politicization of Islamic boarding schools and their role in politics. The data analysis techniques used are content analysis and conceptual analysis with hermeneutics to understand and contextualize al-Abrasyi's thoughts on current realities. The results of the study show: first, al-Abrasyi's concept of Islamic education emphasizes the integral formation of a complete human being that combines spiritual, intellectual, moral, and social aspects, with Islamic boarding schools as bastions of universal Islamic values. Second, various forms of contemporary politicization, such as electoral mobilization, the instrumentalization of kiai, and partisan curricula, are deviations from the essence of education because they reduce pesantren to transactional tools, threaten integrity, and divide communities. Third, as a solution, the ideal principle of the role of pesantren in the public sphere must be based on the ethics of benefit and independence. Pesantren need to function as a moral force by instilling Islamic political ethics, maintaining independence from power, and being active in community empowerment and advocacy for justice. Thus, the influence of pesantren should be built through exemplary behavior and sincere devotion, not pragmatic politicization, in order to be in harmony with the essence of holistic Islamic education.